Alterações de saúde de profissionais de enfermagem em unidades hospitalares - Cavalheiri, Jolana Cristina (2019)
The health work environment provides the cure, care and rehabilitation of the patient, however, when structured in a disorganized way, can contribute to the sickness of the health professional, especially nursing, since this profession remains with the client continuously assistance. For this reason, nursing has a specific illness profile, which occurs because of the way work is organized and exposure to occupational hazards. The objective of this study was to identify the health alterations of nursing professionals in hospital units of a medium size municipality in the South of Brazil. It is a descriptive, exploratory, cross-sectional and quantitative study. Data were collected from February to August 2018, in the work environment of the professionals, using a sociodemographic and occupational profile questionnaire, made up of the research according to pertinent literature and the instruments, Mental Disorders Assessment Questionnaire, the Pittsburgh Sleep Quality Index and the Epworth Sleepiness Scale, validated in the literature. Frequency analysis was used for characterization of the sample and statistical measures. The study sample consisted of 196 nursing professionals, of whom 44 were nurses (22.4%) and 152 nursing technicians (77.6%). The prevalence of females (88.3%), mean age of 37.6 years, white (80.6%), average level of schooling (61.7%), companion (64.3%) and family income of 3 to 5 minimum wages (52%). The professionals reported that they worked in the profession for up to 10 years (55.6%), with more than 6 years in health institutions (65.8%), with only one job (76%), with a workload of up to 40 hours in the week (57.1%). The statutory relationship was predominant (66.8%) for those who worked in the public hospital and service provision (33.2%) in the private hospital. Pittsburgh Sleep Quality Index showed that 49% of the professionals had a poor rating, 27.6% had a sleep disorder and 23.5% had good sleep quality, while 26% had excessive daytime sleepiness and 23% had severe daytime sleepiness. The possibility of a common mental disorder was found in 36.7% of the professionals, who reported feeling nervousness and tension (62.2%), poor sleep (56.6%), frequent headaches (46.4%), and fatigue easily (43.4%), as characteristic symptoms. It is hoped that this study may contribute to the early identification of health changes in health professionals and the monitoring of workers' health.